2021
DOI: 10.13057/biodiv/d220836
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, structure and composition of vegetation in post-coal mining reclamation area in Sumatra, Indonesia

Abstract: Abstract. Yuningsih L, Hearmansyah, Ibrahim E, Marsi. 2021. Diversity, structure and composition of vegetation in post-coal mining reclamation area in Sumatra, Indonesia. Biodiversitas 22: 3392-3400. The majority of coal mines are operated through an open-pit system which has a significant impact on the environment. Therefore, reclamation and revegetation activities are required to recover ecological sustainability. This study aimed to analyze the diversity, structure, and composition of vegetation resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The IVI is a parameter used to measure the ecological significance of a species in a community or a site ( Yuningsih et al . 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IVI is a parameter used to measure the ecological significance of a species in a community or a site ( Yuningsih et al . 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The IVI is a parameter used to measure the ecological significance of a species in a community or a site (Yuningsih et al 2021). The number of plant species recorded in Pagar Gunung and Sopotinjak Resorts at the seedling, understory and sapling stages was 94.…”
Section: Important Value Index (Ivi)mentioning
confidence: 99%
“…The large value of this species diversity index indicates that the stability of the community is getting better. The diversity positively impacts better microclimate and improves soil quality (Yuningsih et al 2021).…”
Section: Vegetation Diversity Index In Revegetation Areas and Natural...mentioning
confidence: 99%
“…This study aimed 1) Analyzing the difference in the wood pellet quality obtained from distinguished types of raw materials and ages; 2) Evaluating the relationship between raw material and wood pellet parameters. Out of the 25 cultivated and natural types of woody plants in South Sumatra, Indonesia, it was found that Enterolobium cyclocarpum, Cassia siamea, and Acacia mangium had the highest dominance value (Yuningsih et al, 2021). This was derived from land revegetation activities, and met the SNI quality standards for all required parameters, including water and ash contents, volatile matter, fixed carbon, compressive strength, and calorific value.…”
Section: Introductionmentioning
confidence: 99%